2013
DOI: 10.1088/1748-9326/8/4/044011
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the East Asian monsoon on lower tropospheric ozone over coastal South China

Abstract: The impact of the East Asian monsoon (EAM) on climatology and interannual variability of tropospheric ozone (O 3 ) over the coastal South China was investigated by analyzing 11 years of ozonesonde data over Hong Kong with the aid of Lagrangian dispersion modeling of carbon monoxide and calculation of an EAM index. It was found that the seasonal cycle of O 3 in the lower troposphere is highly related to the EAM over the study region. Ozone enhancements in the free troposphere are associated with the monsoon-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 30 publications
5
39
0
Order By: Relevance
“…The YRD region is located to the south of the most polluted East China, and under the control of the East Asian Monsoon (Zhou et al, 2013). Long-range and regional transport of the air pollutants have been found to be important factors influencing air quality in this region (Ding et al, 2013a;Lin et al, 2013;Shen et al, 2014;Ding et al, 2016a).…”
Section: Regional Transport and Its Implications For Air Pollution Comentioning
confidence: 99%
“…The YRD region is located to the south of the most polluted East China, and under the control of the East Asian Monsoon (Zhou et al, 2013). Long-range and regional transport of the air pollutants have been found to be important factors influencing air quality in this region (Ding et al, 2013a;Lin et al, 2013;Shen et al, 2014;Ding et al, 2016a).…”
Section: Regional Transport and Its Implications For Air Pollution Comentioning
confidence: 99%
“…No previous studies, to our knowledge, have systematically examined the impacts of the EASM on interannual variations of summertime O 3 in China. Recently, Zhou et al (2013Zhou et al ( ) analyzed 2000Zhou et al ( -2010 ozonesonde data from Hong Kong and found a close link between lower tropospheric O 3 and the East Asian monsoon on interannual scales, but their analyses were focused on O 3 in Hong Kong in spring and autumn. We present here a study to examine the impacts of the EASM on interannual variations of summertime surface-layer O 3 concentrations over China, based on 1986-2006 simulations of O 3 concentrations using the global chemical transport model GEOS (Goddard Earth Observing System)-Chem driven by the assimilated meteorological fields.…”
Section: H Liao Et Al: Interannual Variations Of Summertime Surfacementioning
confidence: 99%
“…Hong Kong is a typical coastal city in the PRD region. Under the influence of the East Asian monsoon, this region is controlled by the southerly winds bringing marine inflow from the South China Sea in summer, while in winter it is downwind from the North China Plains and East China and is dominated by the continental outflow Lam et al, 2001;Zhou et al, 2013). Thus, it is an ideal place for exploring the characteristics of optical properties for continental and marine aerosols.…”
Section: Introductionmentioning
confidence: 99%